L’impegno bucolico di Luigi Alamanni: amore, politica e filologia - Tabacchini, Paolo (Verbum – Analecta Neolatina, 2019)
The article shows the use of bucolic poetry in the works of Luigi Alamanni and examines in particular the author’s application of the traditional stylistic and linguistic device of “bucolic masking”, a typical characteristic of this kind of poetry, which intertwines his biography and his political and cultural commitment.